Pengaruh Gamifikasi Berbasis Media Monopoli terhadap Pemahaman Gramatika Bahasa Arab - Nazilah, Luluk; Syarifuddin, Syarifuddin; Syaifullah, Syaifullah (Borneo Journal of Language and Education, 2025)
Educational media is one of the methods to enhance the teaching and learning process, making students more active in their learning. As a result, the learning outcomes align with expectations. The aim of this study is to investigate the effect of Monopoly-based gamification on students' understanding of Arabic grammar. This study is an experimental research with a one-group pre-test post-test design using a quantitative research method. The research sample consisted of 26 ninth-grade students. The research instruments were pre-test and post-test assessments to measure students' understanding before and after the implementation of the Monopoly media. The results showed a significant improvement in students' grammatical understanding after the implementation of the Monopoly media, with the average pre-test score of 55.96 increasing to 68.27 in the post-test. Normality tests for the pre-test and post-test results showed significant values of 0.149 and 0.116, respectively, both exceeding the threshold of 0.05. This indicates that the data are normally distributed. Furthermore, the paired t-test results showed a two-tailed significance value of 0.001, indicating that Monopoly-based gamification can significantly improve students' understanding of Arabic grammar. The application of Monopoly media also encourages social interaction and collaboration among students in the learning process.